Effects of Continuous Care Model on Depression, Anxiety, and Stress in Iranian Elderly in Shiraz - Sakineh Gholamzadeh; Elahe Pourjam; Majid Najafi Kalyani (Shiraz University of Medical Sciences, 2019)
Background: Psychological disorders such as depression, anxiety, and stress are among the most common health problems in old age. Continuous care and support can be effective and help elderly people to adapt to successive losses, especially if provided within the framework of a model. The present study aimed to determine the effects of the continuous care model (CCM) on depression, anxiety, and stress (DAS) in the Iranian elderly in Shiraz. Methods: The present quasi-experimental study was performed on older adults who attended the Soroush elderly day care center in Shiraz (Iran) from September 2014 to June 2015. A total of 50 eligible elderly participated in the study and were randomly assigned to an intervention group (N=25) and a control group (N=25). The CCM was implemented in the intervention group, whereas the control group received the routine care as offered by the day care center. CCM involves four stages, namely orientation, sensitization, control, and evaluation. The data were collected using the depression, anxiety, stress Scale (DASS-21) questionnaire and a demographic data sheet. The data were analyzed using the SPSS software (version 22.0) with the independent sample t test, paired sample t test, Chi-square test, fisher exact test, multivariate analysis of covariance and the Pearson correlation coefficient. P<0.05 was considered statistically significant. Results: The majority of the participants were women, 44 (88%), with the mean age of 63.4±2.96 years. Following the implementation of the CCM, there was a statistically significant difference in the mean DAS scores between the intervention and control group (P<0.001). Conclusion: The implementation of CCM not only reduced psychological problems (DAS) in the elderly, but also improved and strengthened their psychological condition.